2005
DOI: 10.1103/physrevb.72.155436
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in the Raman RBM and D bands in double-wall carbon nanotubes

Abstract: We have examined several sets of heterogeneous double wall carbon nanotubes and analysed the frequency in a wide range of values. We have found that a statistical correlation exists between the D band intensity and the RBMs intensity. All the sample sets show a correlation of the RBM and D Raman intensity which is monotonic and non-linear using the 514nm laser excitation. Our results suggest that a similar mechanism is at the origin of the RBM and D bands. These results are corroborated by observations on carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…(b) Raman spectra of Double Wall Carbon Nanotubes (DWCNTs) filled with PbI 2 . Reprinted from Ref [498]. with permission.…”
mentioning
confidence: 97%
“…(b) Raman spectra of Double Wall Carbon Nanotubes (DWCNTs) filled with PbI 2 . Reprinted from Ref [498]. with permission.…”
mentioning
confidence: 97%
“…17 For the D band, it was shown that the band is diametersensitive, and in the case of DWCNs one can expect a contribution from both inner and outer tubes, located at different wavenumbers. Unfortunately, the splitting at lower pressures cannot be followed with a diamond pressure cell because of the Raman signal from diamond and the fact that the D band disappears 26 at around 3 GPa. In the DWCNT samples used here, the large diameter distribution leads to a contribution that can be fitted with a single Lorentzian, while with DWCNTs obtained from peapods, the D-band shape is due to a double contribution.…”
Section: Summary Of Pressure-and Temperature-induced Effects Of the Dmentioning
confidence: 99%
“…We note that both the excitation wavelengths used here are not strongly absorbed. 26 A decrease of 10 cm 1 would correspond to a heating of approximately 500°C. But we do not observe any broadening, which should be present if heating does occur.…”
Section: The Effect Of Electron Irradiation On the D Bandmentioning
confidence: 99%
See 1 more Smart Citation
“…No Raman D band is observed for glassy carbon when excited at 257 nm and for DWNTs excited at 325 nm. 5 Radial breathing modes are more difficult to observe due to the spectral cutoff performance of spectrometers in the ultraviolet spectral region.…”
Section: Introductionmentioning
confidence: 99%